2020
DOI: 10.1016/j.cmet.2020.06.017
|View full text |Cite
|
Sign up to set email alerts
|

PHD3 Loss Promotes Exercise Capacity and Fat Oxidation in Skeletal Muscle

Abstract: Rapid alterations in cellular metabolism allow tissues to maintain homeostasis during changes in energy availability. The central metabolic regulator acetyl-CoA carboxylase 2 (ACC2) is robustly phosphorylated during cellular energy stress by AMP-activated protein kinase (AMPK) to relieve its suppression of fat oxidation. While ACC2 can also be hydroxylated by prolyl hydroxylase 3 (PHD3), the physiological consequence thereof is poorly understood. We find that ACC2 phosphorylation and hydroxylation occur in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 66 publications
(78 reference statements)
1
12
0
Order By: Relevance
“…We found that D-allulose administration enhanced the AMPK axis, which is consistent with D-allulose enhancing the oxidation of fatty acids [24,25]. A strong fat-oxidation ability increases the endurance exercise capacity [22]. An increase in fat oxidation following D-allulose administration has been demonstrated in rats [24] and humans [25], which can explain the improved exercise performance observed in the present study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We found that D-allulose administration enhanced the AMPK axis, which is consistent with D-allulose enhancing the oxidation of fatty acids [24,25]. A strong fat-oxidation ability increases the endurance exercise capacity [22]. An increase in fat oxidation following D-allulose administration has been demonstrated in rats [24] and humans [25], which can explain the improved exercise performance observed in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Glycogen in muscles and the liver provides an energy source for aerobic performance [19], and glycogen accumulation can suppress body fatigue during exercise [20]. Alternatively, the efficient use of fat can contribute to exercise performance [21,22] and thus enhance endurance. We hypothesized that D-allulose would enhance exercise performance because its administration has been shown to increase muscle or liver glycogen storage and fat oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that βPHD3KO islets might switch to an alternative energy source to sustain their function, namely, β-oxidation of fatty acids, which are present in excess during HFD feeding. Moreover, in cancer cells, PHD3 has been shown to increase activity of ACC2, which converts acetyl-CoA → malonyl-CoA, the latter suppressing carnitine palmitoyltransferase I (CPT1), the rate-limiting step in fatty acid oxidation ( 24 , 44 ). Indicating a profound change in β cell nutrient preference, supplementation of the culture medium with the fatty acid palmitate for 48–72 hours augmented glucose-stimulated and Extendin-4–potentiated insulin secretion in βPHD3KO islets after 4 weeks HFD ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…In both cases, identifying the PHD3 hydroxylation sites involved will be critical. However, assigning hydroxylation targets using mass spectrometry is currently controversial: misalignment of hydroxylation is frequently associated with the presence of residues in the tryptic fragment that can be artifactually oxidized ( 44 , 50 ). Thus, studies using animals lacking PHD3 and ACC1/ACC2 in β cells, or alternatively the use of (relatively) specific inhibitors, would be required to definitively link the carboxylase with the phenotype here.…”
Section: Discussionmentioning
confidence: 99%
“…Although the focus was on NAFLD and liver function (27), the authors did not report effects on skeletal muscle, that could potentially explain enhanced thermogenesis. For example, a recent study showed that global or skeletal muscle deletion of PHD3 led to enhanced exercise endurance capacity and a small increase in maximum oxygen consumption rate (VO2) due to increased fatty acid oxidation in muscle (30). We cannot directly compare the work by Laitakari et al to our study as they were conducted under different environmental temperatures (RT vs TN), disease (NAFLD vs basal) and genetic models (whole body vs adipose-specific targeting).…”
Section: Loss Of Phd2 In Adipocytes Increases Brown Adipocyte Prolifementioning
confidence: 88%